2012
DOI: 10.1007/s10958-012-0923-z
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic geometry over algebraic structures. II. Foundations

Abstract: MSC 03C99; 08A99; 14A99In this paper we introduce elements of algebraic geometry over an arbitrary algebraic structure. We prove so-called Unification Theorems which describe coordinate algebras of algebraic sets in several different ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 55 publications
0
76
0
1
Order By: Relevance
“…We say that (G, f ) is equational noetherian, if for any system S of polyadic equations, there exists a finite subsystem S 0 such that V G (S) = V G (S 0 ). For general properties of equational noetherian algebraic systems, see [7]. One can define a topology on G m using algebraic sets as a prebase: in this topology every closed set is an arbitrary intersection of finite unions of algebraic sets.…”
Section: Algebraic Geometry Over Polyadic Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…We say that (G, f ) is equational noetherian, if for any system S of polyadic equations, there exists a finite subsystem S 0 such that V G (S) = V G (S 0 ). For general properties of equational noetherian algebraic systems, see [7]. One can define a topology on G m using algebraic sets as a prebase: in this topology every closed set is an arbitrary intersection of finite unions of algebraic sets.…”
Section: Algebraic Geometry Over Polyadic Groupsmentioning
confidence: 99%
“…It can be shown that Y 1 and Y 2 are isomorphic, if and only if, they have the same coordinate polyadic groups. Therefore, it is very important to determine the structure of polyadic groups which are the coordinate polyadic groups of algebraic sets in G. The unification theorems of [7] provide strong tools to do this. Here, we give two versions of the unification theorems which we can use to determine coordinate polyadic groups.…”
Section: Algebraic Geometry Over Polyadic Groupsmentioning
confidence: 99%
See 3 more Smart Citations